Bichitra: Online Tagore Variorum - Caria, Federico (Testo e Senso, 2016)
The digital edition of Rabindranath Tagore, Bichitra: Online Tagore Variorum aims to encompass all of Rabindranath’s literary works in Bengali and English. This edition is an extremely interesting case study for the technical and logistical complexity of the task it sets out to achieve, which involved the development of customised technology and a visualisation strategy to engage the reader with textual variation at both a coarse-grained and a ﬁne-grained level. The edition challenges the role of the literary archive to go beyond being a mere collection of texts and images, and to become instead a set of computational tools that allows the user not only to read but also to interact, explore and visualise the texts.